Comparison of the isometric cervical extension strength and a cross-sectional area of neck extensor muscles in college wrestlers and judo athletes - Tsuyama, K.; Yamamoto, Y.; Fujimoto, H.; Adachi, T.; Nakazato, K.; Nakajima, H. (European Journal of Applied Physiology, 2001)
Increasing neck muscle strength can play an important role in preventing neck injuries in contact sports. The purpose of this study was to examine the actual conditions of the isometric cervical extension strength (ICES) and the cross-sectional area (CSA) of neck extensor muscles in male athletes participating in college wrestling and judo. The subjects comprised 18 wrestlers and 37 judo athletes from Nippon Sports Science University in Japan. The ICES was measured at eight angles (126°, 108°, 90°, 72°, 54°, 36°, 18°, 0°). Transverse slices of 10 mm thickness were obtained at the position of each intervertebral disc between C2 and C3, C3 and C4, C4 and C5 and C5 and C6 using magnetic resonance imaging. The ICES of the wrestlers were significantly higher than those of the judo athletes. The ICES curve against the angle in wrestlers tended to differ from that of judo athletes. The CSA of neck extensor muscles in the wrestlers was significantly larger at all intervertebral levels examined than those of the judo athletes. A significant difference was observed in the CSA of the deepest area of neck extensor muscles between the groups although the difference was not significant in the superficial area. In this study, the ICES and the CSA in wrestlers were shown to be significantly higher and larger respectively than in the judo athletes, indicating a significant difference between these two sports.